Genome-Wide Identification Analysis of the 4-Coumarate: Coa Ligase (4CL) Gene Family in Brassica U’s Triangle Species and Its Potential Role in the Accumulation of Flavonoids in Brassica napus L. - Mengzhen Zhang; Mengjiao Tian; Ziwuyun Weng; Yaping Yang; Nian Pan; Shulin Shen; Huiyan Zhao; Hai Du; Cunmin Qu; Nengwen Yin (Plants)
4-Coumarate: CoA ligase (4CL) is a key branch point enzyme at the end of the phenylpropanoid metabolic pathway. It regulates the synthesis of various metabolites and participates in plant growth and development by catalyzing the formation of CoA ester compounds. However, 4CL family members have not been identified and analyzed among U’s triangle species in Brassica. In this study, 53 4CL genes were identified in Brassica U’s triangle species and divided into 4 groups (group I, II, III and IV) according to phylogenetic relationship. Based on phylogenetics, gene structure, conserved motifs, chromosome localization and collinearity analysis, 4CLs were relatively conserved in the evolution of Brassica U’s triangle species. The promoter region contains a large number of cis-acting elements, implying the functional diversity of 4CLs. Further combining transcriptome data and reverse transcription quantitative PCR (RT-qPCR), we found that Bna4CLs have tissue specificity and can not only respond to exogenous phytohormone changes but also regulate the flavonoid biosynthetic pathway in the yellow- and black-seeded B. napus. Our results complement the lack of research on the 4CL gene family in Brassica, clarify the sequence characteristics and functional diversity of these genes and lay a foundation for further exploration of 4CL genes in response to abiotic stress and regulation of seed coat flavonoid accumulation.